(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Benefits of groundwater availability for human activities in developing countries Groundwater contamination is an important issue, especially given the amount of hydrocarbon water, like that light non-aqueous pasture water (LNAPLs), which migrates and spreads, which contaminates groundwater and makes it unsuitable for domestic and agricultural use. Double-pored soils enable the observation of hydrocarbon liquids diffusing into groundwater. Thus, this work uses computer modeling to measure and predict LNAPL infiltration from physical test data to investigate LNAPL infiltration in double porous soils. LNAPL infiltration parameters and rates described in computers in this example are the practical use of Digital Image Processing Technology (DIPT) and MARA. For calibration and validation purposes, LNAPL volumes of 70 ml and 150 ml were concurrently applied to the the surface of the soil sample. A digital camera was used to capture and monitor the penetration of the two porosities at predetermined intervals. LNAPL penetration patterns were generated on the images using the Matlab program and Surfer software. Data from the physical analyses were used to measure and confirm that LNAPL penetrated the double-pored soil. Consequently, Petrasim’s findings are consistent with the results of the actual experiment. The Nash-Sutcliffe function yields coefficients greater than 0.50 with percentage differences of 2.63% and 3.47% between the actual tests and the Petrasim coefficients, respectively. In conclusion, further investigation of LNAPL infiltration into subsurface soils can be carried out using Petrasim simulation